Smoking, Systemic Arterial Hypertension and Pandemic of COVID-19: A Freudian Psychoanalytical Analysis (Research, Society and Development, 2020)
The objective was to reflect on smoking, its justifications and main influences on the health of hypertensive Primary Care patients in a psychoanalytic perspective. Descriptive, cross-sectional investigation, with reflective analysis structured in Freud's Psychoanalytic Theory, carried out in a Basic Health Unit in Minas Gerais, Brazil, with 40 hypertensive participants. Characterization data, smoking burden profile were collected and individual recorded interviews were conducted. Data processing with content analysis was done with support in SPSS software version 24 and NVivo Pro11. All ethical and legal aspects of research were met. Of the total participants, 40% were smokers / ex-smokers, two discursive categories emerged: 1) Tobacco culture in search of pleasure, satisfaction and tension relief; 2) Smoking cessation and the (de)construction of the everyday reality of the EU in favor of health. Participants are aware of the harmful effects of smoking on their health and quality of life, as well as the increase in their vulnerabilities to being contaminated by the coronavirus.